1997
DOI: 10.1097/00007435-199705000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Human Papillomavirus Infection Detected by Polymerase Chain Reaction Among Urban Canadian Aboriginal and Non-Aboriginal Women

Abstract: No differences were found between AB and non-AB women in the detection of HPV DNA, despite the higher risk for cervical cancer and the prevalence of recognized behavioral and reproductive risk factors among AB women. This study also indicates that the association of sexual activity with HPV infection holds true for both high- and low-oncogenic HPV types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
28
2
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 15 publications
6
28
2
1
Order By: Relevance
“…Women who reported a history of hysterectomy were excluded from the analysis sample (because they are not at risk for cervical cancer). Those that identified themselves as Aboriginal [The sample excluded those that identified as Aboriginal because past studies have reported demographic, health status, and health behaviour differences between Aboriginals and the rest of the Canadian population (Young et al, 1997;McDonald and Trenholm, 2010), and would need to be analyzed separately, which was outside the scope of the study] (i.e., North American Indian, Métis, Inuit) or never had sexual intercourse (because their risk of cervical cancer is very low) were also excluded. Missing data (Missing cases on the CCHS are categorized as 'don't know', 'refused', and 'not stated') on the Aboriginal status, sexual intercourse, and outcome variable were identified and deleted as these variables were used to restrict the sample for analysis.…”
Section: Study Samplementioning
confidence: 99%
“…Women who reported a history of hysterectomy were excluded from the analysis sample (because they are not at risk for cervical cancer). Those that identified themselves as Aboriginal [The sample excluded those that identified as Aboriginal because past studies have reported demographic, health status, and health behaviour differences between Aboriginals and the rest of the Canadian population (Young et al, 1997;McDonald and Trenholm, 2010), and would need to be analyzed separately, which was outside the scope of the study] (i.e., North American Indian, Métis, Inuit) or never had sexual intercourse (because their risk of cervical cancer is very low) were also excluded. Missing data (Missing cases on the CCHS are categorized as 'don't know', 'refused', and 'not stated') on the Aboriginal status, sexual intercourse, and outcome variable were identified and deleted as these variables were used to restrict the sample for analysis.…”
Section: Study Samplementioning
confidence: 99%
“…Limited data on Canadian Aboriginal women indicate that the prevalence of human papillomavirus is not significantly different from that among non-Aboriginal women, although Aboriginal women report higher levels of sexual activity in terms of various indicators such as age at onset, number of lifetime sexual partners and partners in the previous year, and frequency of sexual intercourse. 12 Despite the effectiveness of Papanicolaou test screening, high-risk groups such as Aboriginal women are not participating as frequently as lower risk groups. Such nonparticipation is not only the result of lack of information; it is also due to cultural and gender-related factors.…”
Section: Discussionmentioning
confidence: 99%
“…6,10,11 The church is the most important social institution of the African American community. 7,12,13 Sixty-one percent of African American adults attend religious services at least once a month, a rate substantially higher than that among Whites (47%). 8 Churches have a similarly central role in the Latino community, where "lowacculturated, Spanish-speaking, poorly educated women can be reached with health education messages."…”
Section: Contributorsmentioning
confidence: 99%
“…The overall prevalence of HPV-16 and HPV-18 was 11.6%, while in women younger than 20 years of age it was 16.7% (9). A study (10) in Inuit women, 13 to 20 years of age, found a higher prevalence of HPV infection of 31.7%, although another study (11) did not find increased risk in Aboriginal women in Winnipeg, Manitoba, when compared with their nonAboriginal counterparts.…”
Section: Hpv Epidemiologymentioning
confidence: 93%